Assessment of angiospermic diversity with earlier flora of Ambala district, Haryana (India) - DR. MANDEEP KAUR (International Journal of Pharma and Bio Sciences, 2019)
The assessment of plant diversity could play an important role in planning conservation strategies and sustainable use of available resources. A total of 414 plant species belonging to the 294 genera and 90 families were recorded from this area. Considerable reduction in the number of members of Cyperaceae, Scrophulariaceae and Solanaceae has been observed in the study area when compared. The phytogeographical analysis of data of Ambala district reveals that tropical Indian elements form the major part (ca 44 %) of the flora of Ambala district, this is followed by American, Cosmopolitan whereas Australian, Mediterranean, African, Malayan and Himalayan and temperate elements are equally represented. During survey it has been noticed that the changing environmental conditions, human activities and introduction of invasive species are resulting in the loss of native floristic diversity of the area. As a result of habitat fragmentation and habitat destruction some of species such as Gloriosa superba, Oroxylum indicum, Clitoria ternatea, Sphagneticola calendulacea, Martynia annua, Bacopa monnieri, Heliotropium strigosum, Pentatropis nivalis and Plumbago zeylanica are in queue for becoming extinct in the future from the study area as these has been reported at one or two study sites in the district.